'Being' in the coaching world: new insights on youth performance coaching from an interpretative phenomenological approach. Issue 8 (17th November 2017) - Cronin, Colum; Armour, Kathleen M.
ABSTRACT: Since Heidegger's influential text; Being and time (1927/2005), the phenomenological question of what it means to 'be' has generated a vast body of work. This paper reports data from a phenomenological study that investigated what it means to 'be' a youth performance coach. An overview of the interpretive phenomenological methods used is followed by presentation of coaches and data. Data analysis resulted in the identification of three constituent 'essences' of youth performance coaching: (i) care; (ii) a commitment to educate athletes authentically for corporeal challenges to come; and (iii) working with others to achieve a specialised corporeal excellence. The three identified essences manifest themselves in a broad lifeworld that includes settings on and off the field of play (FOP). Given the very different insights into the practice of coaching that emerge from this study, we argue it would be useful for future studies of coaching practice and coach education to extend their focus to take into account coaches' wider lives both on and off the FOP. We also argue for further exploration of coaching by drawing on phenomenological concepts such as care and relationality.